Multidisciplinary Management of Patients with Psoriatic Arthritis: The Role of the Dermatologist and the Rheumatologist - F.F. Azizova; M.N. Karzhavova (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Psoriatic arthritis (PsA) is a chronic immune-mediated inflammatory disease of the musculoskeletal system that develops in 20–30% of patients with psoriasis. The condition lies at the intersection of two specialties—dermatology and rheumatology—which often leads to diagnostic delays averaging 6–7 years. Late diagnosis and delayed initiation of pathogenetic therapy are associated with irreversible joint destruction, functional impairment, and a significant reduction in patients’ quality of life.